Modeling of EDM Process parameters for Machining Stainless Steel using Copper Electrodes - Khan, Ahsan Ali; Abdulkareem, Suleiman (Freund Publishing House Ltd., 2008)
This paper reports on the experimental investigations of surface roughness and material removal rate in electrical discharge machining (EDM) of austenic stainless steel. The importance of this study is that it establishes imperical relations regarding machining parameters and the responses in analyzing the machinability of the austenitic stainless steel. The machining factors used are current intensity (I), pulse on-time (ti), pulse off-time (to) and gap voltage (v), over the important factors of surface roughness (Ra) and material removal rate (MRR). The investigation and the analysis of the influences of machining parameters on the response variables were performed by using the technique of design of experiments (DOE). The developed models show that current intensity and pulse on-time are the most significant machining parameters influencing Ra and MRR while increase in off-time results in decrease MRR response. These models can be used to get the desired responses within the experimental range.